Effect of aloe emodin on the gene expression profiling in human glioma cell lines - Yusoff, Abdul Aziz Mohamed (Universiti Sains Malaysia, 2014)
Aloe emodin has been previously reported to promote anticancer activity via inhibning the expression of several genes. This study was aimed to investigate the apoptosis and cell cycle arrest inducing by aloe emodin on U87 human malignant glioma cells as well as to explore its effect on the gene expression profile of U87 cells by utilizing microarray technology. In this study: aloe emodin showed a time:. and dose dependent inhibition of U87 cells proliferation and decreased \he percentage of viable U87 cells via the induction of apoptosis. Characteristic morphological changes, such as the formation of apop!otic bodies, were observed with confocal microscope by Annexin V-FITC/PI' staining, supporting our viability study and flow cytometry analysis results. Our data also demonstrated that ~loe emodin arrested the cell cycle in the S phase and promoted the loss of mitochondrial membrane potentiill in U87 cells that indicated the early event of the mitochondria-induced apoptotic pathway. Microarray analy~is also reported that more than 8,000 gene expression alterations out of 28,000 gene-label probe sets were detected after treatment with 58.6 fJg/ml aloe emodin concentration for 24 hour. However, only 34 genes were; considered statistically significant (p<0.05). Interpretation of microarray data revealed 22 genes that were up-regulated and 12 genes that were downregulated in response to aloe emodin treatment. This study demonstrates that expression of genes in glioma cells affected by aloe emodin involved in various cellular functions mainly in cell proliferation and apoptosis . These results could serve as guidance for further studies in order to recover molecular targets for targeted cancer therapy-based aloe emodin treatment. Besides that the Involvement of certain genes in the formation and progression of brain tumors need further evaluation.